Validation of EpiTRAQ, a transition readiness assessment tool for adolescents and young adults with epilepsy. Issue 3 (12th August 2020) - Clark, Sarah J.; Beimer, Nicholas J.; Gebremariam, Acham; Fletcher, Linda L.; Patel, Anup D.; Carbone, Lorrie; Guyot, Jamie A.; Joshi, Sucheta M.
Abstract: Objective: To design and validate a transition readiness assessment tool for adolescents and young adults with epilepsy and without intellectual disability. Methods: We adapted a general transition readiness assessment tool (TRAQ) to add epilepsy‐relevant items based on concepts in current epilepsy quality measures. The adapted tool, EpiTRAQ, maintained the original structure and scoring system. Concurrent with clinical implementation in pediatric and adult epilepsy clinics at an academic medical center, we assessed the validity and reliability of this adapted tool for patients 16‐26 years of age. This process included initial validation with 302 patients who completed EpiTRAQ between October 2017 and May 2018; repeat validation with 381 patients who completed EpiTRAQ between June 2018 and September 2019; and retest reliability among 153 patients with more than one completed EpiTRAQ. Results: Mean scores were comparable between initial and repeat validation populations (absolute value differences between 0.05 and 0.1); internal consistency ranged from good to high. For both the initial and repeat validation, mean scores and internal consistency demonstrated high comparability to the original TRAQ validation results. Upon retest, few patients rated themselves with a lower score, while the majority rated themselves with higher scores. Significance: EpiTRAQ is a valid and reliable tool for assessing transition readiness in adolescents and young adults with epilepsy and without intellectual disability.